2018
DOI: 10.1159/000490194
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Sulfur-Containing Amino Acids Are Associated with Higher Prevalence of Overweight/Obesity in Northern Chinese Adults, an Internet-Based Cross-Sectional Study

Abstract: Background/aims: Elevation of plasma sulfur-containing amino acids (SAAs) is generally associated with higher body mass index (BMI) and unfavorable lipid profiles. It is not known how dietary SAAs relate to these associations in humans. Methods: A convenient tool named internet-based dietary questionnaire for Chinese (IDQC) was used to estimate dietary SAAs intake. A total of 936 participants were randomly recruited and asked to complete the IDQC. Furthermore, 90 subjects were randomly selected to perform a su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 40 publications
2
10
0
Order By: Relevance
“…Furthermore, we found SCAAs to be positively associated with BMIz, WHtR, and fat mass, which remained significant even after controlling for several other possible confounders. Our results confirm the findings of a study done on Chinese adults, which showed an association between SCAA intake and BMI and waist circumference [68]. For both of these amino acid groups, we only estimated the dietary intake.…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, we found SCAAs to be positively associated with BMIz, WHtR, and fat mass, which remained significant even after controlling for several other possible confounders. Our results confirm the findings of a study done on Chinese adults, which showed an association between SCAA intake and BMI and waist circumference [68]. For both of these amino acid groups, we only estimated the dietary intake.…”
Section: Discussionsupporting
confidence: 90%
“…In addition to taurine, the amino acids methionine and cysteine from which taurine can be produced (see Section 2.3 ) have been associated with obesity and metabolic syndrome [ 207 , 221 , 222 ], and the modulation of the bioavailability of sulphur-containing amino acids might provide further benefits, e.g., by stimulating the synthesis of the antioxidant glutathione (discussed in [ 203 ]).…”
Section: Discussionmentioning
confidence: 99%
“…Third, unfortunately, data regarding dietary intake were not available to corroborate our results. However, it has recently been proved that higher dietary sulfur-containing amino acids are associated with higher prevalence of obesity, insulin resistance, and inflammation [60].…”
Section: Discussionmentioning
confidence: 99%